Between hope and fear: developing social media guidelines. Issue 2 (13th February 2017) - Opgenhaffen, Michaël; Claeys, An-Sofie
Abstract : Purpose: The purpose of this paper is to examine employers' policy with regard to employees' social media use. Specifically, the authors examine the extent to which employers allow the use of social media in the workplace, what opportunities can be related to employees' social media use and how social media guidelines are implemented within organizations. Design/methodology/approach: In-depth interviews were conducted with HR and communication managers of 16 European companies from different sectors and of varying size. Findings: Some organizations believe that social media should be accessible to employees while others ban them from the workplace. Most respondents believe that organizations can benefit from employees sharing work-related content with their own network. However, they encourage the sharing and retweeting of official corporate messages rather than employees developing their own messages. This fear regarding employees' messages on social media is reflected in the broad adoption of social media guidelines. Research limitations/implications: Future research should chart the nature of existing social media guidelines (restrictive vs incentive). Accordingly, the perceived sense and nonsense of social media guidelines in companies should be investigated, not only among the managers but also among employees. Practical implications: Organizations should remain in dialogue with employees with regard to social media. Managers seem overly concerned with potential risks and forget the opportunities that can arise when employees operate as ambassadors. Originality/value: The use of in-depth interviews allowed the authors to assess the rationale behind social media guidelines within organizations in depth and formulate suggestions to organizations and communication managers.